The capital goods sector in Developing Countries : technology issues and policy options - United Nations Conference on Trade and Development (New York : United Nations, 1985)
The study deals with technology issues at two different but equally critical phases of the development of a capital goods sector in developing countries: namely; problems associated in the initial phase with the first entry into capital goods production, and problems facing those countries which have already developed some capital goods production capability and wish now to move forward into the design and manufacture of complex capital goods.
"UNCTAD/TT/78"--T.p. verso.
"United Nations publication sales no. E.85.II.D.4"--T.p. verso.
ne 09/04/2018
Loans
Keywords: Machine-tool industry; Industrial equipment industry; Machinery industry; Developing countries